Eksplorasi Implementasi Circle Time pada Sekolah Dasar yang Menerapkan Gerakan Sekolah Menyenangkan: Exploration of Circle Time Implementation in Elementary Schools of Gerakan Sekolah Menyenangkan - Rizqi Hanabella; Theresia Novi Poespita Candra (Universitas Negeri Surabaya, 2021)
This study aims to explore the effectiveness of circle time method as perceived by both teachers and students in the elementary schools that implement